استخدام قلف بعض الأشجار كمراكم حيوي لتقييم تلوث الهواء بعنصر الرصاص في مدينة طرطوس (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
This research was carried out during 2016 and aimed to using the outer bark of  some species (Citrus aurantium - Ligustrum vulgaris - Melia azedrach) in Tartous city as bioaccumulators for assessing lead air pollution. The results showed an increased accumulation of lead on tree bark in the summer compared to winter in all locations. It is arranged as follows: Dowar alsiyah > Street of 6 Tishreen > Baitte kamoni (rural region) > Street of Althowra. The highest concentration of lead (Pb) was found in the bark of Ligustrum vulgaris followed by the Citrus aurantium and then Melia azedrach. We noted a positive and significant correlation between the lead values and the electrical conductivity of the bark extract in the summer. In conclusion, we can say that the bark of Ligustrum vulgaris tree is a good bioaccumulator for the Pb element. أُجري هذا البحث خلال عام 2016 بهدف استخدام القسم الخارجي من قلف بعض الأنواع الشجرية (الزفير Citrus aurantium – اللوغستروم Ligustrum vulgaris – الأزدرخت Melia azedrach) المنتشرة في مدينة طرطوس كمراكمات حيوية لتقييم تلوث الهواء بعنصر الرصاص. أظهرت النتائج زيادة تراكم عنصر الرصاص على قلف الأشجار في فصل الصيف مقارنةً بفصل الشتاء في جميع المواقع. وهي مرتبة على النحو التالي: موقع دوّار السياحة > موقع شارع 6 تشرين > موقع بيت كمونة (منطقة ريفية) > موقع شارع الثورة. كما لوحظ أن أعلى تركيز للرصاص (Pb) كان في قلف شجرة اللوغستروم يليه قلف الزفير ثم قلف الأزدرخت، ولوحظ وجود علاقة ارتباط معنوية موجبة بين قيم الرصاص والناقلية الكهربائية لمستخلص القلف في فصل الصيف. بالخلاصة يمكننا القول إن شجرة اللوغستروم تعد مراكم حيوي جيد لعنصر الــ Pb.